Minimized Cost Gateway Deployment in Cyber-Physical Systems - Hao Wang; Jianzhong Li; Hong Gao (International Journal of Distributed Sensor Networks)
Wireless networks have been widely used in Cyber-Physical System (CPS) for data transmission. A CPS usually contains lots of sensors, and these sensors generate massive data. To make use of these data, we have to collect them through wireless communication. Sensors in a certain CPS do not always adopt same wireless technology, and these sensors formed heterogeneous wireless networks. Communication between different types of wireless networks can only be achieved by utilizing wireless gateways. In this paper, we address the problem of gateway placement for satisfying the bandwidth-requirement of each node by using minimum gateways. This problem can be formulated as a variant of Minimum Geometric Disk Cover problem which has been proved NP-complete. In order to solve our problem, one heuristic gateway placement algorithm and one grid-based heuristic algorithm are proposed. The result of simulation demonstrates that the heuristic algorithm can offer a good solution with big probability.